1971
DOI: 10.1017/s0022112071002246
|View full text |Cite
|
Sign up to set email alerts
|

On stability of Taylor vortices by fifth-order amplitude expansions

Abstract: Davey, Di Prima & Stuart's (1968) double amplitude expansion for disturbances in flow between concentric cylinders is formulated in matrix notation. The stability of the secondary equilibrium (Taylor-vortex) flow is calculated using fifth-order terms in amplitude, and using the full equations rather than the small-gap approximation. Qualitative confirmation is found of instabilities to the Taylor-vortex flow to non-a.xisymmetric disturbances at about 10 % above the first critical Taylor number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…We follow Eagles [5] and write the disturbance equations in dimensionless matrix form as follows. We set u = u', v = v s + v', w = w s + w', p =Ps + P' and ignore terms of O(e4).…”
Section: The Perturbation Equations In Matrix Formmentioning
confidence: 99%
See 2 more Smart Citations
“…We follow Eagles [5] and write the disturbance equations in dimensionless matrix form as follows. We set u = u', v = v s + v', w = w s + w', p =Ps + P' and ignore terms of O(e4).…”
Section: The Perturbation Equations In Matrix Formmentioning
confidence: 99%
“…We need to use the adjoint eigenfunction as defined in Eagles [5]. This is denoted by f~ where aL ~---~ + { A~') }trL = O.…”
Section: Solutions Of the Disturbance Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Taylor vortices were shown to develop due to a linear inviscid instability of the base flow, putting experiment and theory in good agreement with one another and providing some hope that the phenomena of transition and turbulence may be theoretically understood. Taylor's experiments sparked a flurry of research activity, which includes the following: theoretical studies of Taylor vortex instability such as Davey et al (1968) and Eagles (1971), who used weakly nonlinear analysis to determine the instabilities which affect Taylor vortices; experimental papers such as Coles (1965), Andereck et al (1986) and Hegseth et al (1996), who mapped in parameter space the different flow regimes observed in the experiments; and numerical stability analyses wherein finite-amplitude Taylor vortices are calculated numerically in addition to the higher-order structures they bifurcate towards, such as Nagata (1988), Weisshaar et al (1991) and Antonijoan & Sánchez (2000). Recent experimental attention has been focused on the flow of a differentially rotated fluid through a linear shear layer, known as rotating plane Couette flow (RPCF), a review of which can be found in Mullin (2010).…”
Section: Introductionmentioning
confidence: 99%
“…They computed the cubic coefficients in their model (without exploiting symmetry to simplify the calculations). The fifth-order coefficients were obtained by Eagles (1971). The reduction to a 6-dimensional model was not justified rigorously; indeed they worked with a fixed outer cylinder, where the requisite mode interaction does not actually occur.…”
Section: A N D R E W H I L L a N D I A N S T E W A R Tmentioning
confidence: 99%